2018
DOI: 10.1016/j.pep.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Rapid NMR-scale purification of 15N,13C isotope-labeled recombinant human STIM1 coiled coil fragments

Abstract: We report a new NMR-scale purification procedure for two recombinant wild type fragments of the stromal interaction molecule 1 (STIM1). This protein acts as a calcium sensor in the endoplasmic reticulum (ER) and extends into the cytosol accumulating at ER - plasma membrane (PM) junctions upon calcium store depletion ultimately leading to activation of the Orai/CRAC channel. The functionally relevant cytosolic part of STIM1 consists of three coiled coil domains, which are mainly involved in intra- and inter-mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Structurally, all STIM1 monomers contain an N-terminal signal peptide, a canonical Ca 2+ -binding EF 1 hand, a non-Ca 2+binding EF 2 hand, and a sterile α-motif (SAM) domain in the ER luminal region (known as ER-SAM) (Dziadek and Johnstone, 2007;Schober et al, 2019). The C-terminus domain located in the cytosolic side of the ER membrane is characterized by the coiled-coil 1 (CC1) segments, a STIM-Orai-activating region (SOAR) or calcium release-activated calcium (CRAC) activation domain (CAD), and the motif S/TxIP which are the components of the Orai1 activation small fragment Stathopulos et al, 2013;Rathner et al, 2018; Figure 2).…”
Section: Store-operated Ca 2+ Entrymentioning
confidence: 99%
“…Structurally, all STIM1 monomers contain an N-terminal signal peptide, a canonical Ca 2+ -binding EF 1 hand, a non-Ca 2+binding EF 2 hand, and a sterile α-motif (SAM) domain in the ER luminal region (known as ER-SAM) (Dziadek and Johnstone, 2007;Schober et al, 2019). The C-terminus domain located in the cytosolic side of the ER membrane is characterized by the coiled-coil 1 (CC1) segments, a STIM-Orai-activating region (SOAR) or calcium release-activated calcium (CRAC) activation domain (CAD), and the motif S/TxIP which are the components of the Orai1 activation small fragment Stathopulos et al, 2013;Rathner et al, 2018; Figure 2).…”
Section: Store-operated Ca 2+ Entrymentioning
confidence: 99%
“…The focus is on competitive interactions of cytosolic domains of STIM. The recently published functional data as well as structural data from nuclear magnetic resonance (NMR) spectroscopy and molecular dynamics (MD) simulations have been essential in advancing and complementing the characterization of STIM [15,21,22,30]. Moreover, we report results of ongoing functional investigations that are based on these novel NMR data.…”
Section: Introductionmentioning
confidence: 97%
“…However, three point mutations were required because purification of the wild-type form was challenging (Yang et al, 2012). Very recently, Rathner et al reported an optimized protocol for one-step purification of cytosolic OASF ext (aa 234-491), which is similar to CC1-CAD-IDstim (Rathner et al, 2018). Thus, a structural study to demonstrate the intramolecular interaction of IDstim should be carried out in the near future.…”
Section: Discussionmentioning
confidence: 99%